2021
DOI: 10.1002/cpt.2263
|View full text |Cite
|
Sign up to set email alerts
|

Nested Case‐Control Study Utilizing MID‐NET® on Thrombocytopenia Associated With Pegfilgrastim in Patients Treated With Antineoplastic Agents

Abstract: Although several spontaneous case reports on the occurrence of thrombocytopenia in patients treated with human granulocyte colony-stimulating factor (G-CSF) preparations have been accumulated, its actual causality is still unclear. To investigate the association between G-CSF preparations (filgrastim, nartograstim, lenograstim, and pegfilgrastim) available in Japan and thrombocytopenia in patients treated with antineoplastic agents, a nested case-control study was conducted using the Medical Information Databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…With respect to adverse events other than FN, the incidence of grade 3 or higher thrombocytopenia in our study was higher than that in the Japanese modified FOLFIRINOX study (22.7 vs. 2.9%). Kajiyama et al reported from a large national database, that pegfilgrastim increased the risk of thrombocytopenia in Japanese patients treated with antineoplastic agents [25]. Therefore, as not only the doses of FOLFIRINOX, but also the dose of pegfilgrastim could have had an influence on the incidence of severe thrombocytopenia, careful attention should be paid when adding pegfilgrastim administration to the modified FOLFIRINOX regimen for Japanese patients with PC.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to adverse events other than FN, the incidence of grade 3 or higher thrombocytopenia in our study was higher than that in the Japanese modified FOLFIRINOX study (22.7 vs. 2.9%). Kajiyama et al reported from a large national database, that pegfilgrastim increased the risk of thrombocytopenia in Japanese patients treated with antineoplastic agents [25]. Therefore, as not only the doses of FOLFIRINOX, but also the dose of pegfilgrastim could have had an influence on the incidence of severe thrombocytopenia, careful attention should be paid when adding pegfilgrastim administration to the modified FOLFIRINOX regimen for Japanese patients with PC.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we selected the NDB as a data source for these studies. MID-NET R is usually selected for a study in which laboratory test results are necessary for analysis (29)(30)(31)(32). As described above, an understanding of the characteristics of each database is important to select a data source fit to a study purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Using routinely collected medical claims data, this observational study using a nested case-control study design [ 27 – 29 ] was conducted following the STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) guidelines [ 30 ], RECORD (Reporting of Studies Conducted Using Observational Routinely-Collected Health Data) Statement [ 31 ], and ethical standards of the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%